Association of anesthetic and surgical risk factors with outcomes of initial diagnostic biopsies in a current cohort of children with anterior mediastinal masses. Issue 5 (27th October 2021) - Halepota, Huma Faiz; Tan, Josephine S K; Reddy, Satish K; Tang, Phua Hwee; Ong, Lin Yin; Lee, York Tien; Chan, Mei Yoke; Soh, Shui Yen; Chang, Kenneth T E; Ng, Agnes S B; Loh, Amos Hong Pheng
Abstract : Background: Diagnostic biopsies of pediatric anterior mediastinal masses (AMMs) are high-risk procedures in which general anesthesia (GA) is traditionally avoided. However, awareness of historically recognized risk factors and corresponding perioperative management have improved over time and may now no longer strictly preclude the use of GA. Therefore, in this study, we examined the association of anesthetic and surgical risk factors and modalities with resulting procedural and survival outcomes in a current patient cohort. Methods: We retrospectively reviewed charts of 35 children with AMMs who underwent initial diagnostic biopsies between January 2001 and August 2019, and determined tracheal compression and deviation from archival CT scans and procedural and disease outcomes. Results: Twenty-three (65%) patients underwent GA while 12 (35%) received sedation. Among patients with available CT measurements, 13 of 25 (52%) had >50% anteroposterior tracheal diameter reduction. Patients with >50% anteroposterior tracheal compression received sedation more frequently (p=0.047) and were positioned upright (p=0.015) compared with patients with ≤50% compression, although 4 of 13 and 9 of 12, respectively, still received GA. Intraoperative adverse events (AEs) occurred in four (11.4%) patients: three received GA, and all were positioned supine or lateral. AEs were not associated with radiographic airway risk factors but were significantly associated with morphine and sevoflurane use (p<0.001) and with thoracoscopic biopsies (p=0.035). There were no on-table mortalities, but four delayed deaths occurred (three related to disease and one from late procedural complications). Conclusions: In a current cohort of pediatric AMM biopsies, patients with >50% anteroposterior tracheal compression were more frequently managed with a conservative perioperative management strategy, though not completely excluding GA. The corresponding reduction in frequency of procedural AEs in this traditionally high-risk group suggests that increased awareness of procedural risk factors and appropriate risk-guided perioperative management choices may obviate the procedural mortality historically associated with pediatric AMM biopsies.